Adaptive mechanisms of athletes’ bodies under extreme conditions - Denisenko, Yu.P.; Ahmetov, A.M.; Semenov, S.A.; Andrushchishin, I.F. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to provide theoretical and experimental justification for the basic principles of constructing a comprehensive system of special relaxation training aimed at improving the functional state of athletes’ bodies, increasing the rate of skeletal muscle relaxation, and improving the effectiveness of the training process. Methods and structure of the study. The dynamics of hypoxic resistance, the rate of voluntary relaxation (RVR) of skeletal muscles, and the power of the braking-relaxation functional system of urgent adaptation and protection (BRFSP) of the body from extreme influences during long-term adaptation to various adaptogenic factors were studied. All subjects were divided into two groups: group 1 consisted of athletes with initially high BRFSP capacity (experimental), and group 2 consisted of athletes with initially low BRFSP capacity (control). The purpose of this grouping was to determine the influence of the initial BRFSP power on the nature of long-term adaptation of the parameters under consideration under the influence of various adaptogenic factors. Results and conclusions. An increase in the activity of the central nervous system’s braking systems and muscle RVR, as an urgent adaptive response to intense physical exertion, occurs when BRFSP is activated by extreme influences. The dependence of muscle character and RVR on the functional state of the central nervous system has been demonstrated. The functional state of the central nervous system also largely determines the power of BRFSP. The results of the studies provide a basis for the methods and principles of special relaxation training aimed at increasing the effectiveness of the training process.